Working in an urgent dental care hub during the Covid-19 pandemic from a dental nurses' perspective. (2nd February 2022) - Plessas, Anastasios; Paisi, Martha; Baines, Rebecca; Wheat, Hannah; Delgado, Maria Bernardes; Mills, Ian; Witton, Robert
Abstract : A qualitative study